SOCS3: an essential regulator of LIF receptor signaling in trophoblast giant cell differentiation - Takahashi, Yutaka (Oxford University Press, 2003)
Suppressor of cytokine signaling 3 (SOCS3) binds cytokine receptors and thereby suppresses cytokine signaling. Deletion of SOCS3 causes an embryonic lethality that is rescued by a tetraploid rescue approach, demonstrating an essential role in placental development and a non-essential role in embryo development. Rescued SOCS3-deficient mice show a perinatal lethality with cardiac hypertrophy. SOCS3-deficient placentas have reduced spongiotrophoblasts and increased trophoblast secondary giant cells. Enforced expression of SOCS3 in a trophoblast stem cell line (Rcho-1) suppresses giant cell differentiation. Conversely, SOCS3-deficient trophoblast stem cells differentiate more readily to giant cells in culture, demonstrating that SOCS3 negatively regulates trophoblast giant cell differentiation. Leukemia inhibitory factor (LIF) promotes giant cell differentiation in vitro, and LIF receptor (LIFR) deficiency results in loss of giant cell differentiation in vivo. Finally, LIFR deficiency rescues the SOCS3-deficient placental defect and embryonic lethality. The results establish SOCS3 as an essential regulator of LIFR signaling in trophoblast differentiation.